Padroado e soberania nas concordatas latino-americanas: Costa Rica, Argentina e Brasil no Pontificado de Pio IX - Santirocchi, Ítalo Domingos (Revista Brasileira de História das Religiões, 2025)
The article investigates the concordat negotiations between the Holy See and three Latin American countries during the pontificate of Pius IX, focusing on the tensions between padroado (royal patronage) and national sovereignty. Using the Bolivian model (1851) and its developments as a reference, it demonstrates that the Costa Rican Concordat (1852) was successful because it recognized padroado as a privilege granted by the pope, accompanied by free communication with Rome, the restoration of ecclesiastical jurisdiction, protection of Church property, and freedom for religious orders. In contrast, negotiations with Argentina and Brazil failed, as both governments upheld padroado as a right inherent to national sovereignty (including beneplácito/exequatur and state control over the Church). In the Argentine case, a modus vivendi was established to enable episcopal appointments without renouncing the principle; in the Brazilian case, a "war of narratives" prevailed between the 1824 Constitution and the papal bull Praeclara Portugalliae (1827). The analysis, grounded in the Connected History approach, reveals how these negotiations were embedded in a transnational network of disputes between civil and ecclesiastical powers, highlighting the selective success of Pius IX’s concordat policy where governments agreed to recentralize papal authority within the newly independent national churches.